2014
DOI: 10.7860/jcdr/2014/8024.4021
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of Premenstrual Syndrome, A Systematic Review and Meta-Analysis Study

Abstract: IntrOductIOnToday, research on women's health has greatly improved [1,2]. PMS is a common health problem in women in reproductive age and defined as a collection of emotional symptoms, with or without physical symptoms, related to a woman's menstruation cycle [3]. PMS is occur during the luteal phase of menses, however, it disappear with menstrual flow. The prevalence of PMS has been reported in 20 to 32 % of premenopausal [4] and 30-40% of the reproductive female population [5].There are several different sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
62
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(74 citation statements)
references
References 22 publications
4
62
1
1
Order By: Relevance
“…One study using the PMS scale reported a 36.4% rate among nursing students [6] . PMS prevalence has also been reported to be 47.8% in a recently published meta-analysis [1] . PMS prevalence rates can vary due to cultural characteristics, sample differences, and diagnostic methods.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…One study using the PMS scale reported a 36.4% rate among nursing students [6] . PMS prevalence has also been reported to be 47.8% in a recently published meta-analysis [1] . PMS prevalence rates can vary due to cultural characteristics, sample differences, and diagnostic methods.…”
Section: Introductionmentioning
confidence: 88%
“…Premenstrual syndrome (PMS) is characterized by physical and mental symptoms during the luteal phase of the menstrual cycle; however, symptoms improve rapidly with the onset of menstruation [1] , [2] , [3] . PMS is commonly seen in women of reproductive age and can be accompanied by emotional and physical symptoms [1] . The prevalence of PMS is approximately 20–32% of premenopausal women [4] and 30–40% in reproductive women [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 This prevalence varies in relation to the population studied and the type of assessment tool used: 37.5% in Arabian women, 3 17.5% in Japanese women, 4 25.2%, 5 43.3%, 6 and 97.2% 7 in Brazilian women, and 41% in American women, 8 with the lowest incidence, about 10%–12%, in Europe, while Asia has the highest percentage, with 98%. 9 Some factors may influence PMS, such as age, menstrual cycle characteristics, socioeconomic and educational levels, use of hormonal contraceptives, and lifestyle, including diet, habits, and physical activities. 10 , 11 PMS has been considered a syndrome of multifactorial origin, and is related to the increase of inflammatory reactions and oxidative stress and an inadequate overproduction of nitric oxide, as well as superactivation of the renin–angiotensin– aldosterone system, possibly due to hormone changes.…”
Section: Introductionmentioning
confidence: 99%
“…Premenstrual syndrome (PMS) refers to a set of physical, emotional, and behavioral symptoms that occur periodically in women during the late luteal phase of the menstrual cycle, peaking within the week preceding menses and improving or disappearing after the onset of menses (1)(2)(3). A meta-analysis study revealed the prevalence rate of PMS is as high as 47.8% (4). Given the high proportion of women who experience PMS, its etiology has attracted considerable attention among researchers in recent years (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%